2017
DOI: 10.1093/jtm/tax010
|View full text |Cite
|
Sign up to set email alerts
|

Infection burden among medical events onboard cargo ships: a four-year study

Abstract: These data illustrate a previously underreported variability of the medical risks in various maritime routes; and help promoting targeted medical interventions including the implementation of onboard point-of-care laboratories, to further increase the rapidity of the diagnosis and the medical management onboard cargo ships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 11 publications
0
17
1
Order By: Relevance
“…Studies show that a non-negligible proportion of infections that occur on board are dental. 6,26 The proportion of tooth decay (33% of dental cases in the present study) is relatively low compared with the study by Sobotta et al, which found a diagnostic of tooth decay in 85% of dental emergencies. 27 This difference may be caused by bias in the diagnostic categories.…”
Section: Management Of Oral Emergencycontrasting
confidence: 77%
See 2 more Smart Citations
“…Studies show that a non-negligible proportion of infections that occur on board are dental. 6,26 The proportion of tooth decay (33% of dental cases in the present study) is relatively low compared with the study by Sobotta et al, which found a diagnostic of tooth decay in 85% of dental emergencies. 27 This difference may be caused by bias in the diagnostic categories.…”
Section: Management Of Oral Emergencycontrasting
confidence: 77%
“…Another study shows that 7% of infections on board are dental infections. 6 A dental emergency is the first reason why sailors are referred to a specialist onshore. [5][6][7] Sailors may remain at sea for several days or weeks with short periods onshore.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aircraft and vessels at maximum capacity, in confinement condition, facilitates the dissemination from person to person by droplets and aerosols, besides introducing new viruses in new areas after landing 3,4 . But unlike cruise ships 4 , there is no recent record of the involvement of cargo ships in the spread of the disease 3,5 .…”
Section: Discussionmentioning
confidence: 99%
“…Seafarers are an unusual group of workers with specific health concerns and medical care needs. On one hand, to be allowed to work on board a ship, they need to pass regular, typically annual or biannual, medical examinations 12–14 . Furthermore, all ships have a standardized set of medical equipment 14 .…”
Section: Introductionmentioning
confidence: 99%